The Law of Taklif (Mukallaf) in Business - Amaliah Handina; Xu Zhiyong (Journal of International Islamic Business Studies, 2025)
All human actions, behavior, and words are closely linked to the requirements of Sharia law, whether derived from the Qur'an, Sunnah, or other sources recognized by Sharia. According to Imam al-Ghazali, rulings on sharia are the essence of Islamic jurisprudence (fiqh) and ushul fiqh (jurisprudence). The goal of these two disciplines is to understand the activities of the mukallaf. Humans are stressed in terms of the legal demands of Taklif to be carried out or demands to be abandoned, which of course demands to be carried out are called obligatory and recommendations to be carried out are called sunnah. Meanwhile, demands to abandon certain things are called haram (forbidden), and recommendations to abandon them are called makruh (reprehensible). These legal demands emphasize human action in all aspects of life, including in the context of business.